2015
DOI: 10.1017/s0022215115000766
|View full text |Cite
|
Sign up to set email alerts
|

Sphenopalatine foramen: endoscopic approach with bony landmarks

Abstract: Determination of reliable bony landmarks is clinically useful in endoscopic surgery and can aid identification of the sphenopalatine foramen. The inferior turbinate concha and posterior fontanelle may be used as reliable computed tomography landmarks for endoscopic approaches to the sphenopalatine foramen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…The dimensions of the SPF (3.79-6.44 mm) were smaller than those reported in the literature (4.62-6.8 and 7.5-9.35 mm) 16,17 . Also, the vertical distance between the SPF and palatum durum (or nasal floor) was reported as 15.58 mm that is less than those reported in the literature ranging from 18.27 to 26.6 mm 8,18 .…”
Section: Discussioncontrasting
confidence: 65%
“…The dimensions of the SPF (3.79-6.44 mm) were smaller than those reported in the literature (4.62-6.8 and 7.5-9.35 mm) 16,17 . Also, the vertical distance between the SPF and palatum durum (or nasal floor) was reported as 15.58 mm that is less than those reported in the literature ranging from 18.27 to 26.6 mm 8,18 .…”
Section: Discussioncontrasting
confidence: 65%
“…From these, we selected and have made reference in the text to the following article types: systematic reviews, n = 3; 8 , 15 , 16 narrative reviews or algorithms, n = 8; 11 , 17 23 randomised controlled trials, n = 3; 24 26 non-randomised controlled studies, n = 4; 1 , 27 29 case series or cohort studies, n = 9; 30 – 38 surveys and audits, n = 5; 9 , 10 , 14 , 39 , 40 cost-effectiveness studies, n = 5; 12 , 13 , 41 43 anatomy studies, n = 6; 44 – 49 case reports, n = 5; 50 – 54 and historical articles, n = 6 2 7 …”
Section: Resultsmentioning
confidence: 99%
“…The sphenopalatine artery exited as expected from the foramen in only 3 of 19 specimens (16 per cent), whereas it exited either much more posteriorly or from a distinct foramen directly posterior to the normal one in 8 specimens (42 per cent) 48 . A recent prospective analysis of 102 computed tomography scans of the paranasal sinuses suggested that the inferior turbinate concha and the posterior fontanelle are reliable landmarks for the sphenopalatine foramen 49 …”
Section: Discussionmentioning
confidence: 96%
“…The PPG is the largest peripheral parasympathetic ganglia and is triangular in shape [14,15]. It is located deep within the PPF and lies lateral to the SPF and below and slightly medial to the foramen rotundum and the maxillary nerve [15] (Figs.…”
Section: Anatomy Of the Ppgmentioning
confidence: 99%